2007
DOI: 10.1016/j.exger.2007.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Aging in adipocytes: Potential impact of inherent, depot-specific mechanisms

Abstract: Fat mass and tissue distribution change dramatically throughout life. Fat depot sizes reach a peak by middle or early old age, followed by a substantial decline, together with fat tissue dysfunction and redistribution in advanced old age. These changes are associated with health complications, including type 2 diabetes, atherosclerosis, dyslipidemia, thermal dysregulation, and skin ulcers, particularly in advanced old age. Fat tissue growth occurs through increases in size and number of fat cells. Fat cells tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
217
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(231 citation statements)
references
References 82 publications
9
217
0
5
Order By: Relevance
“…Biological aging has profound effects in every major adipose tissue depot (Cartwright et al 2007;Huffman and Barzilai 2009;Tchkonia et al 2010). The loss of subcutaneous white adipose tissue (WAT) or lipodystrophy in the elderly leads to thinning of the skin, impairing its mechanical resilience, and increasing the risk for bed-sores or decubitus ulcers during prolonged periods of bed rest (Davies 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biological aging has profound effects in every major adipose tissue depot (Cartwright et al 2007;Huffman and Barzilai 2009;Tchkonia et al 2010). The loss of subcutaneous white adipose tissue (WAT) or lipodystrophy in the elderly leads to thinning of the skin, impairing its mechanical resilience, and increasing the risk for bed-sores or decubitus ulcers during prolonged periods of bed rest (Davies 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The loss of subcutaneous white adipose tissue (WAT) or lipodystrophy in the elderly leads to thinning of the skin, impairing its mechanical resilience, and increasing the risk for bed-sores or decubitus ulcers during prolonged periods of bed rest (Davies 1994). Visceral WAT accumulates with advancing age in men and women (Weisberg et al 2003;Ortega et al 2008;Gavi et al 2007), and inflammatory processes within visceral WAT place the elderly at increased risk for metabolic syndrome, diabetes, and cardiovascular disease (Trayhurn and Beattie 2001;Trayhurn 2005;Cartwright et al 2007;Huffman and Barzilai 2009). Recent evidence indicates that thermogenic brown fat decreases with age and this change contributes to obesity (Nedergaard et al 2007;Cypess et al 2009;van Marken Lichtenbelt et al 2009;Virtanen et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The notion of lipid storage over-capacity is supported by several studies in which cultured preadipocytes from old animals consistently showed reduced lipid accumulation, reduced lipogenic enzyme activities, and changes in differentiation-dependent gene expression (Djian et al 1985;Hauner et al 1989;Gregerman 1994;Karagiannides et al 2001;Cartwright et al 2007). Since adipogenesis is a result of transcriptional activities, a better way to understand the above-mentioned shift is to examine the molecular events involved in adipogenesis that are modulated by the activation of a large number of adipose-related genes (Fève 2005).…”
mentioning
confidence: 97%
“…Although the underlying mechanisms are not known, peripheral subcutaneous fat tends to decrease with age, whereas visceral fat does not seem to be affected (Hughes et al 2004;Cartwright et al 2007).…”
mentioning
confidence: 98%
See 1 more Smart Citation